Caracterização e estudo comparativo de uma nova cepa de Clostridioides difficile isolada de um hospital oncológico de Fortaleza, Ceará - Costa, Cecília Leite (2017)
Clostridioides difficile is a strictly anaerobic, spore-forming, toxin-producing Gram positive bacillus which is recognized to be the major cause of nosocomial diarrhea associated with antibiotic therapy. The aim of this study was to characterize a new strain of C. difficile (ICC45) isolated from a patient in a cancer hospital in Fortaleza and compare with the strains ATCC 700057 (non-toxigenic) and NAP1/027 (R20291 and LIBA5756, hypervirulent strains). The strains isolated from patients admitted to Haroldo Juaçaba Hospital, from the Cancer Institute of Ceará (HHJ of the ICC) were processed to phenotypic identification and detection of toxin genes and the tpi gene fragment by PCR. The susceptibility of the strains to eight antimicrobial agents was determined by E-test. Molecular identification analyses of the strains were performed by PFGE, PCR ribotyping and toxinotyping. In addition, Whole Genome Sequencing, Multilocus sequence typing (MLST), relative gene expression of the virulence factors, and protein expression of toxins A and B were performed by Western Blotting in strain ICC45 in comparison with NAP1/027. In all isolates of HHJ of the ICC, the tpi, tcdA and tcdB genes were detected. The binary toxin binding domain (cdtB) was detected in strain ICC45, but no tcdC gene deletions were observed in any of the isolates. Three isolates were from the same genotype and ribotype, NAP4/014-020 and toxinotype XVIII. The ICC45 strain was assigned to a new PCR ribotype and new pulsotype and was classified as ST41 of MLST Clade 2 and toxinotype IXb. ICC-45 encodes a variant TcdB. Unlike NAP1/027, which also belongs to MLST Clade 2, ICC-45 is susceptible to fluoroquinolones and does not overproduction of toxins A and B at 24 hours of culture. The relative gene expression of the tcdA, tcdB, cdtA, cdtB and tcdC genes was higher in the ICC45 strain. ICC45 exhibited increased expression in fliA (p<0.0001) compared to NAP1 and ATCC. fliC and fliD genes were expressed only by the ICC45 strain. The ICC45 strain also showed higher expression of spo0A (p<0.0002) and cwp84 (p<0.0001) compared to NAP1 and ATCC. The overexpression of relative genes of these virulence factors by ICC45 may have contributed to the severity of the patient's disease and tissue injury and inflammatory process similar to that caused by NAP1 in animal model, previously described. The data presented here highlight the importance of studying the epidemiological situation and the emergence of new strains of C. difficile in Brazilian hospitals.